Assessing trunk flexo-extension during sit-to-stand test variant in male and female healthy subjects through inertial sensors - Roldán-Jiménez, Cristina; Cuesta-Vargas, Antonio; Bennett, Paul (Taylor & Francis, 2019)
Objective: The objective of the present study was to measure trunk flexo-extension during different Sit-To-Stand (STS) tasks and to analyze differences in those variables when STS repetitions are increased, by using an inertial sensor. Methods: In this cross-sectional study trunk flexo-extension was obtained through inertial measurements using an inertial sensor placed on the flat part of the sternum with the Y transversally oriented and attached using double-sided adhesive tape. Trunk flexo-extension was expressed along the Y axis (pitch angle) in a sagittal plane, representing antero-posterior motion (degrees, °). Descriptive anthropometric independent variables were also recorded. Subject had to sit and rise from a 43 cm high chair at a speed of 40 bpm in 5, 10 and 15 repetitions of STS variants. Results: Men showed higher mean mobility (between 41.51° and 43.23°) than women (between 32.16° and 33.31°) in all STS test, although significant was only found for 10-STS and 15-STS (<0.05). Male gender showed stronger Pearson correlation between each test than female gender. In men, correlations were highly significant in all tests (r between 0.891 and 0.939). However, in the case of women, significance varied between each test comparison (r between 0.474 and 0.745). There were no significant differences observed between trunk flexo-extension and STS variants (p = 0.908; F = 0.097). Conclusion: Men showed a wider range of trunk motion and a more consistent pattern than women through STS variants. However, no significant differences were found in mobility between each test. The results provided in this study should be taken into account when performing STS in this population and should be applied only to a healthy population.
https://openpolicyfinder.jisc.ac.uk/id/publication/33274
Keywords: Biomecánica; Kinesiología; Biomechanical phenomena; Kinematics; Motion analysis; Sit-to-stand